Antibiotic and Surgical Treatment of a Ventriculoperitoneal Shunt-Related Soft Tissue Abscess Caused by Brucella melitensis - Joost Boeckmans; Koen Magerman; Steven Vanvolsem; Reinoud Cartuyvels; Luc Waumans; Peter Messiaen (Annals of Internal Medicine: Clinical Cases)
We report on the antibiotic and surgical treatment of a woman who presented with an abscess caused by Brucella melitensis related to a ventriculoperitoneal shunt, which is an atypical presentation of brucellosis. There were no signs of neurologic, osteoarticular, or peritoneal infection. The abscess initially healed after ultrasound-guided drainage and antibiotic treatment with gentamycin/doxycycline for 5 days, followed by doxycycline/ciprofloxacin for 8 weeks, allowing shunt preservation. Three months after treatment ended, however, a relapse occurred that required partial surgical shunt revision and readministration of antibiotics. Seven months after surgery and 12 months after the initial diagnosis, the patient's remission status has been maintained.